Representation of Nationhood and Social Change in Bari Adetunji Arabic Short Stories - Akewula, Adams Olufemi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract Arabic short stories have long been a powerful medium for exploring themes of nationhood and social change. This article examines the theme of nationhood and social change in the Arabic short stories of Shaykh Bari Adetunji contained in “fuhusu-l-Afais fi funun-l-Aqosis”. Through a literary analysis of his work, this article explores how Adetunji’s narratives challenge traditional notions of nationhood and advocate for social transformation. By examining the complex characters,the role of the Arabic short story in shaping nationhood and facilitating social change in the Arab world. Through a critical analysis of selected short stories, we examine how this literary genre reflects and influences societal transformations, challenges dominant narratives, and offers a platform for marginalized voices. Our discussion highlights the power of the Arabic short story in fostering critical thinking, cultural identity, and collective action, ultimately contributing to the evolution of nationhood and social progress.